Liquidity traps and monetary policy: Managing a credit crunch - Francisco Buera; Juan Pablo Nicolini (Federal Reserve Bank of Chicago, 2014)
We study a model with heterogeneous producers that face collateral and cash in advance constraints. These two frictions give rise to a non-trivial financial market in a monetary economy. A tightening of the collateral constraint results in a credit-crunch generated recession. The model can suitable be used to study the effects on the main macroeconomic variables - and on welfare of each individual - of alternative monetary - and fiscal - policies following the credit crunch. The model reproduces several features of the recent financial crisis, like the persistent negative real interest rates, the prolonged period at the zero bound for the nominal interest rate, the collapse in investment and low inflation, in spite of the very large increases of liquidity adopted by the government. The policy implications are in sharp contrast with the prevalent view in most Central Banks, based on the New Keynesian explanation of the liquidity trap.
Keywords: 330